Pemberian Diet Diabetes Melitus Kardiovaskular pada Pasien Diabetes Melitus dengan Pneumonia dan Parkinson: Sebuah Laporan Kasus - Paskahrani Fedra Aurelia; Azizah Ajeng Pratiwi; Yuyun Eka Sari (Universitas Airlangga, 2024)
Background: Diabetes mellitus is a disease that occurs due to metabolic disorders in the pancreas characterized by increased blood sugar levels in the body or also known as hyperglycemia. The presence of a history of high blood pressure can increase the risk of experiencing severity. Someone who has diabetes mellitus has a higher risk of infection. The standardized Nutrition Care Process (NCP) is carried out by providing a cardiovascular diabetes mellitus diet. Objectives: To determine the management of standardized nutritional care in patients with cardiovascular diabetes mellitus diet in patients with diabetes mellitus with pneumonia and Parkinson's disease. Methods: The case study was conducted in October 2022 at RSI Jemursari Surabaya. Sampling using purposive sampling Results: After monitoring and evaluation, the results found that the laboratory results were still high, the physical/clinical condition was getting better, but dental pain and shortness of breath that worsened when coughing on the third day returned. The patient's intake increased from day to day, but there were still some macronutrient fulfillments that could not reach the target (<80%). Conclusions: The recovery of the patient's condition was not good enough, the results of biochemical and physical/clinical monitoring still showed fluctuating changes, but in food intake, there is an increase.